2016
DOI: 10.1038/cddis.2016.165
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 facilitates skeletal muscle regeneration by balancing pro- and anti-inflammatory macrophages

Abstract: Skeletal muscle has remarkable regeneration capacity and regenerates in response to injury. Muscle regeneration largely relies on muscle stem cells called satellite cells. Satellite cells normally remain quiescent, but in response to injury or exercise they become activated and proliferate, migrate, differentiate, and fuse to form multinucleate myofibers. Interestingly, the inflammatory process following injury and the activation of the myogenic program are highly coordinated, with myeloid cells having a centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 80 publications
6
46
0
1
Order By: Relevance
“…Human monocytes/macrophages M1 IFN-, LPS, GM-CSF, TNF-CXCL9, IL-12 high/IL-10 low, iNOS, IL-6, CD80, CD86, TNF-Pro-inflammation, microbicidal effect, tumor resistance 1,2,6-8,11,27,63,105 M2a IL-4, IL-13 CCL17, IL-1R, CD206, Dectin-1, IL-10, DC-SIGN Anti-inflammatory, wound in macrophages contributes to the increased production of CCL2 and TNF by directly repressing B-cell lymphoma-6 (BCL6) expression and the reduced expression of Arg-1 and Chil3. 100,101 By contrast, increased miR-223 promotes M2 polarization. 102 miR-222 plays a crucial role in M2b polarization.…”
Section: Phenotypes Stimuli Markers Functions Referencesmentioning
confidence: 97%
See 1 more Smart Citation
“…Human monocytes/macrophages M1 IFN-, LPS, GM-CSF, TNF-CXCL9, IL-12 high/IL-10 low, iNOS, IL-6, CD80, CD86, TNF-Pro-inflammation, microbicidal effect, tumor resistance 1,2,6-8,11,27,63,105 M2a IL-4, IL-13 CCL17, IL-1R, CD206, Dectin-1, IL-10, DC-SIGN Anti-inflammatory, wound in macrophages contributes to the increased production of CCL2 and TNF by directly repressing B-cell lymphoma-6 (BCL6) expression and the reduced expression of Arg-1 and Chil3. 100,101 By contrast, increased miR-223 promotes M2 polarization. 102 miR-222 plays a crucial role in M2b polarization.…”
Section: Phenotypes Stimuli Markers Functions Referencesmentioning
confidence: 97%
“…Recent studies have shown that miR‐21, miR‐125a‐3p, miR‐146a, miR‐147, miR‐214, and miR‐455 are up‐regulated in M1 macrophages, whereas miR‐let7c, miR‐143‐3p, miR‐145‐5p, and miR‐193 are more abundant in M2 macrophages . The up‐regulation of miR‐155 in macrophages contributes to the increased production of CCL2 and TNF by directly repressing B‐cell lymphoma‐6 (BCL6) expression and the reduced expression of Arg‐1 and Chil3 . By contrast, increased miR‐223 promotes M2 polarization…”
Section: Modulation Of M2b Macrophage Polarizationmentioning
confidence: 99%
“…Satellite cells, muscle resident stem cells, become activated to proliferate, migrate to the injury, fuse, and differentiate to form new myofibers (13,14). Mφs directly control satellite-cell activation and maturation and are crucial to muscle regeneration (15,16). M1 Mφs promote the proliferation of satellite and myogenic precursor cells, in vitro and in vivo, following human muscle injury, while M2 Mφs promote their differentiation (15).…”
mentioning
confidence: 99%
“…M1 Mφs promote the proliferation of satellite and myogenic precursor cells, in vitro and in vivo, following human muscle injury, while M2 Mφs promote their differentiation (15). Imbalanced Mφ polarization, specifically skewing toward M1 phenotypes, has been shown to inhibit skeletal muscle repair (3,16,17). Transition to M2 phenotypes is critical to ultimately yield functional muscle (18).…”
mentioning
confidence: 99%
“…This miR appears to be essential to the balance between pro-inflammatory M1 macrophages and anti-inflammatory M2 macrophages during skeletal muscle regeneration and could be a target molecule to degenerative muscle diseases [139]. However, further studies are necessary to evaluate the involvement of miR-155 during skeletal muscle adaptation in response to physical exercise Masi et …”
Section: Physical Exercise Induced-mirs and Immune Functionmentioning
confidence: 99%